A spiritual perestroika: religion in the late Soviet parliaments, 1989-1991 - Sablin, Ivan (Entangled Religions, 2022)
The article discusses various meanings which were ascribed to religion in the parliamentary debates of the perestroika period, which included Christian, Muslim, Buddhist, and other religious and lay deputies. Understood in a general sense, religion was supposed to become the foundation or an element of a new ideology and stimulate Soviet or post-Soviet transformations, either creating a new Soviet universalism or connecting the Soviet Union to the global universalism of human rights. The particularistic interpretations of religion viewed it as a marker of difference, dependent on or independent of ethnicity, and connected to collective rights. Despite the extensive contacts between the religious figures of different denominations, Orthodox Christianity enjoyed the most prominent presence in perestroika politics, which evoked criticisms of new power asymmetries in the transformation of the Soviet Union and contributed to the emergence of the Russian Federation as a new imperial, hierarchical polity rather than a decolonized one.